2021
DOI: 10.1002/cmdc.202100291
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 Inhibitors for Epitranscriptomic Modulation of Cellular Processes

Abstract: The methylase METTL3 is the writer enzyme of the N 6 -methyladenosine (m 6 A) modification of RNA. Using a structure-based drug discovery approach, we identified a METTL3 inhibitor with potency in a biochemical assay of 280 nM, while its enantiomer is 100 times less active. We observed a dose-dependent reduction in the m 6 A methylation level of mRNA in several cell lines treated with the inhibitor already after 16 h of treatment, which lasted for at least 6 days. Importantly, the prolonged incubation (up to 6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 53 publications
1
99
0
Order By: Relevance
“…4 ) was identified. It was further validated to selectively bind to METTL3 by X-ray crystallography, and it slightly suppresses the expression of METTL3 but significantly reduces m6A levels in the mRNA fraction in the leukemia cell line MOLM-13 and human osteosarcoma U2OS cells [ 216 ].…”
Section: Drug Discovery Of M6a Modulatorsmentioning
confidence: 99%
“…4 ) was identified. It was further validated to selectively bind to METTL3 by X-ray crystallography, and it slightly suppresses the expression of METTL3 but significantly reduces m6A levels in the mRNA fraction in the leukemia cell line MOLM-13 and human osteosarcoma U2OS cells [ 216 ].…”
Section: Drug Discovery Of M6a Modulatorsmentioning
confidence: 99%
“…STM2457 can prevent AML expansion and impair leukemia stem cells in both a patient-derived xenograft (PDX) model and a primary mouse MLL-AF9/Flt3 itd/+ model ( 78 ). Another METTL3 -selective inhibitor, UZH1a, a high-nanomolar inhibitor, occupies the SAM binding site of METTL3 , similar to STM2457 ( 79 ). UZH1a could also result in a decrease in the mRNA m 6 A methylation level in AML MOLM-13 cells in a dose-dependent manner (IC50 of 7 µM) ( 79 ).…”
Section: The Potential Application In Cancer Therapymentioning
confidence: 99%
“…Another METTL3 -selective inhibitor, UZH1a, a high-nanomolar inhibitor, occupies the SAM binding site of METTL3 , similar to STM2457 ( 79 ). UZH1a could also result in a decrease in the mRNA m 6 A methylation level in AML MOLM-13 cells in a dose-dependent manner (IC50 of 7 µM) ( 79 ). Furthermore, this group also confirmed that UZH1a could reduce mRNA m 6 A/A levels not only in the leukemia cell line MOLM-13 but also in other cell lines (osteosarcoma U2OS cells and immortalized human embryonic kidney cell line HEK293T).…”
Section: The Potential Application In Cancer Therapymentioning
confidence: 99%
“…No cellular data were obtained in Bedi’s work. To date, there are two different selective small molecule inhibitors of METTL3, namely, STM2457 and UZH1a, which were independently reported by Yankova et al and Moroz-Omori et al [ 146 , 147 ]. When binding with METTL3, the two inhibitors both occupy the SAM-binding site and reorganize Lys 513 of METTL3, which partly contributes to their selectivity.…”
Section: Opportunities For Application Of M6a Modification In Ocmentioning
confidence: 99%
“…Consistently, SAM and sinefungin, pan inhibitors of methyltransferases, do not possess a specific binding mode [ 148 ]. Although the activity of STM2457 and UZH1a in OC is still unknown, both STM2457 and UZH1a could dampen the activity of METTL3 in the AML cell line MOLM-13 [ 146 , 147 ]. Moreover, the propagation of several AML cell lines from human or mouse was blocked by STM2457 [ 146 ].…”
Section: Opportunities For Application Of M6a Modification In Ocmentioning
confidence: 99%